2021
DOI: 10.52198/22.sti.40.os1591
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Periarticular Multimodal Analgesic Injection Containing High-Dose Ketorolac versus Triamcinolone in Early Postoperative Total Knee Arthroplasty: A Randomized Controlled Trial

Abstract: Introduction: Periarticular multimodal analgesic injection associates with less postoperative (post-op) pain after total knee arthroplasty (TKA) with less opioid consumption. The combination of additives and dosage are various and controversial. Evidence of ketorolac compared to triamcinolone as an additive is limited in terms of efficacy and safety. Materials and Methods: Fifty-six patients with unilateral TKA were randomized to receive either 60mg ketorolac or 80mg triamcinolone acetonide as cocktail additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Meta-analysis included 3 high-quality studies [ 31 , 52 , 67 ] with ketorolac as an additive to PAI in TKA only 30 mg periarticular infiltration Various Intraoperative PAI with Ketorolac leads to decrease postoperative pain, but effect on opioid usage is unclear – 2/3 studies found no difference in opioid usage with the addition of ketorolac. The addition of Ketorolac to PAI contain long-acting analgesics provides additional benefit compared to PAI without ketorolac Various Apinyankul et al [ 39 ] RCT 56 patients receiving TKA 1. 60 mg Ketorolac as an additive to unspecified PAI cocktail 2.…”
Section: Ketorolac (Toradol)mentioning
confidence: 99%
See 3 more Smart Citations
“…Meta-analysis included 3 high-quality studies [ 31 , 52 , 67 ] with ketorolac as an additive to PAI in TKA only 30 mg periarticular infiltration Various Intraoperative PAI with Ketorolac leads to decrease postoperative pain, but effect on opioid usage is unclear – 2/3 studies found no difference in opioid usage with the addition of ketorolac. The addition of Ketorolac to PAI contain long-acting analgesics provides additional benefit compared to PAI without ketorolac Various Apinyankul et al [ 39 ] RCT 56 patients receiving TKA 1. 60 mg Ketorolac as an additive to unspecified PAI cocktail 2.…”
Section: Ketorolac (Toradol)mentioning
confidence: 99%
“…Ketorolac's recommended IM and IV dose is 30 mg as a one-time dose or 30 mg every 6 h up to a maximum total of 120 mg in 24 h [ 51 ]. Still, some studies also describe 60 mg as a dosage option[ 39 , 40 ] with a possible dose-dependent response [ 49 , 52 ]. Many studies included visual analog scale (VAS) scores and opioid usage as measures of effectiveness for postoperative pain management.…”
Section: Ketorolac (Toradol)mentioning
confidence: 99%
See 2 more Smart Citations
“…Periarticular infiltration (PI) is widely performed during TKA. It involves the intraoperative injection of a local anesthetic combined with other medications, such as nonsteroidal anti-inflammatory drugs (NSAIDs) or steroids, into the soft tissue around the knee joint [ 12 , 13 ]. A periarticular injection can be administered by the surgeon intraoperatively and at a low cost [ 14 ].…”
Section: Introductionmentioning
confidence: 99%